36.1k views
0 votes
Solve for x: 3 − (2x − 5) < −4(x + 2)

1 Answer

3 votes

Hello!

Solving inequalities is just like solving regular algebraic equations. You need to use SADMEP, which is an acronym for subtraction, addition, division, multiplication, exponents and parentheses.

Although, when you are dividing by a negative number, the inequality symbol is flipped. It is self-explanatory (< → >, > → <, ≤ → ≥, ≥ → ≤).

3 - (2x - 5) < -4(x + 2) (apply the distributive property to both sides)

3 - 2x + 5 < -4x - 8 (simplify - add)

8 - 2x < -4x - 8 (subtract 8 both sides)

-2x < -4x - 16 (add 4x to both sides)

2x < - 16 (divide both sides by -2)

x < -8

Therefore, the values of x are x values less than -8.

User Vela
by
6.0k points